Air‐Water Mixing in Vegetated Supercritical Flow: Effects of Vegetation Roughness and Water Temperature on Flow Self‐Aeration. Issue 2 (14th February 2022) - Bai, Ruidi; Bai, Zhongtian; Wang, Hang; Liu, Shanjun
Abstract: Vegetated flow is rarely investigated for supercritical flow regime, in which self‐aeration occurs and modifies the flow dynamics, energy dissipation, and mass transfer between the water body and ambient air environment. In this study, natural river water was used at two flow rates in combination with six bottom vegetation conditions to investigate the air‐water flow development in an 18‐m‐long sloping chute. The vegetation configurations included two artificial turfs with different grass lengths and three flexible plant covers with different canopy densities, in addition to a reference case of smooth solid boundary, providing flow resistance and turbulent disturbance with different orders of equivalent roughness heights. Physical measurements were focused on the air concentration, free‐surface splashing, turbulent velocity, bubble count frequency, and bubble size distributions from the upstream non‐aerated flow to the far‐field fully developed aeration region. Compared to the velocity developing to uniform equilibrium shortly downstream the inception of aeration, the flow self‐aeration reached air‐concentration equilibrium at further downstream positions, while the bubble count and air‐water interfacial area kept increasing. The vegetation roughness conditions affected the inception location, equivalent bubble rise velocity, superfacial splashing height, velocity gradient, and maximum bubble count near the free surface, whereas the equilibrium air concentration in the fully developed region depended only upon the slope. The vegetation type influenced the percentage of submillimetre bubbles. Little differences were shown in the air‐water flow characteristics by repeating the summer experiments in winter with a 25.5°C drop in water temperature, despite the variation in fluid viscosity thus the Reynolds number under identical discharge. Plain Language Summary: When water flows at a relatively high speed, for example, down a slope, it entrains air into the water body through its breaking free surface. The mix of air with water leads to a change in the fluid properties thus the flow behavior. The presence of vegetation on the bottom of the flow is known to enhance this air‐water interplay. In this work, we try to understand how the different vegetation types (grass and saplings) and densities would affect the air‐water flow development down a sloping chute, by measuring detailed air‐water flow properties using an intrusive phase‐detection probe. We further repeat the same outdoor experiments in summer and winter to gain a preliminary idea about the possible influence of the water temperature on the results. Key Points: Air entrainment is studied experimentally in supercritical flow over various bottom vegetation configurations Bottom vegetation roughness modifies substantially the aerated flow hydraulics, air‐water flow properties, and bubble characteristics No influence of water temperature on air‐water mixing is observed in summer and winter seasons